2005
DOI: 10.1140/epjb/e2005-00237-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cascading failures in the North American power grid

Abstract: The North American power grid is one of the most complex technological networks, and its interconnectivity allows both for long-distance power transmission and for the propagation of disturbances. We model the power grid using its actual topology and plausible assumptions about the load and overload of transmission substations. Our results indicate that the loss of a single substation can lead to a 25% loss of transmission efficiency by triggering an overload cascade in the network. We systematically study the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
365
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(377 citation statements)
references
References 31 publications
4
365
0
8
Order By: Relevance
“…Finding network topologies that enhance the stability of power grids has been an active subfield of network theory. Previous studies have typically focused on the structural vulnerability of power grids against external attacks [1][2][3][4][5][6][7] and the cascading spreading of system failure over power grids [6,[8][9][10]. In addition, researchers have studied the relation between topology and dynamics via network synchronization models.…”
Section: Introductionmentioning
confidence: 99%
“…Finding network topologies that enhance the stability of power grids has been an active subfield of network theory. Previous studies have typically focused on the structural vulnerability of power grids against external attacks [1][2][3][4][5][6][7] and the cascading spreading of system failure over power grids [6,[8][9][10]. In addition, researchers have studied the relation between topology and dynamics via network synchronization models.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has studied the relationship between a network ′ s structure and its topological resilience to incremental node loss [24] and the relationship between average degree and the effect of single node damage [10]. It was shown that the larger the average node degree, the less stable a steady state is against single node damage.…”
Section: Resultsmentioning
confidence: 99%
“…The question is then under which conditions this failure leads to a cascade of macroscopic size. Applications of this case include power-grid cascade failures [4,5,10], or failures of server infrastructure [6].…”
Section: Results For the Rie Regimementioning
confidence: 99%
“…A fixed relation between fragility and threshold was first used in [4] to describe cascading processes in power grids and Internet (see also [5,9,10]). It basically reflects the situation of many socio-technical systems in which the capacity of agents is usually ad hoc designed to handle the load, because limited by cost, under normal conditions.…”
Section: /23mentioning
confidence: 99%